Integrating GraphRAG and GIS for Cultural Heritage Digitization: A Case Study of Jiangbei District - Xu, Mingfei; Jia, Weichen (Cultural Arts Research and Development, 2025)
With the rapid advancement of digital technologies, the preservation and management of cultural heritage face both new opportunities and challenges. Jiangbei District in Ningbo, Zhejiang Province, is home to a substantial number of immovable cultural relics requiring systematic documentation and scientific oversight. In response to the Fourth National Cultural Relics Survey, this study proposes a data-driven approach to support the digital management and sustainable use of these resources.The research adopts a structured methodology encompassing data collection, organization, analysis, and exploration. Through the curation of both historical and newly acquired records—including combing, cleaning, and filtering—a complete framework was developed. Based on this, a digital platform was constructed to integrate, manage, and visualize cultural heritage data.Visualization techniques were employed to present the spatial distribution and associative characteristics of heritage sites, facilitating intuitive understanding and enhancing decision making capabilities. The resulting platform supports structured data management, enabling more effective cultural relic protection, knowledge inheritance, and cross-sectoral application.Beyond technical outcomes, the platform also contributes to public engagement and education by improving accessibility and promoting awareness of cultural heritage. This broader societal impact supports not only the long-term preservation of local culture but also encourages community involvement and cultural literacy.Overall, this study lays a foundation for the digital transformation of cultural heritage work in Jiangbei District and offers a replicable model for other regions seeking to combine heritage protection with modern digital methodologies. It provides both a practical management tool and a reference for interdisciplinary research and heritage-based development initiatives.